Analisis Status Gizi Lansia dengan Beberapa Teknik Pengukuran Tinggi (tinggi lutut (knee height), Panjang Depa (arm span), dan Tinggi Badan (stature) di Padang Tahun 2015 - Irma Eva Yani; John Amos .; Defriani Dwiyanti . (Jurnal Sehat Mandiri, 2017)
The increase in the number of seniors influence aspects of their lives. As a result of the aging process occurs with age is a decrease in bone mass that can alter the bone structure. Making it difficult to determine the nutritional status of the elderly, especially in determining badan.Tinggi height and weight used to measure body mass index (BMI) .Some known method to predict the height, among others, using the range of arm (arm span), and high-knee , The purpose of this study to look at the nutritional status of elderly people in ethnic Minang whether there is a difference by using variations in measurements at a different height with knee height), arm span, and stature. This research is an analytic study with cross sectional study design in Padang start of June - August 2015 in elderly aged> 60 years amounted to 81 people. Data collected in the form of weight data is measured using digital bathroom scales, height is measured by means microtoise, Knee Height is measured with a caliper in a sitting position, and fathoms long with a tool arm span and tested by independent ANOVA test.The results showed an average elderly for weight of 54.3 kg, stature of 151.5 cm, conversion knee height of 156.3 cm, arm span of 156.7 cm. The average BMI for stature of 23,2, knee height of 22.35 and arm span of 22.9. The average nutritional status with KMS for stature of 23,2, knee height of 21.75 and arm span of 21.37. There are differences in stature to the height of the knee in women and there are no differences in stature with a high knee in men. As for arm span there is a difference in stature of both men and women. There is no difference in the nutritional status of elderly with BMI and which refers to the KMS elderly. The absence of the differences in nutritional status, so it is advisable to health workers to take measurements of nutritional status of elderly with high measurement adapted to the conditions of the elderly. If the elderly can stand up to do the measurement of stature and if the elderly can not stand up well to do with stature measurements with the knee or arm span.